ANALISIS KEBUTUHAN PENGEMBANGAN LKPD BERBASIS PROJECT BASED LEARNING (PJBL) BERMUATAN SOSIOSAINTIFIK UNTUK FASE E PADA MATERI PERUBAHAN DAN PELESTARIAN LINGKUNGAN - Rahmawati; Arsih, Fitri; Fuadiyah, Sa'diatul; Olvia Rahmi, Fitri (Universitas Cokroaminoto Palopo, 2024)
The development of student worksheet for biology learning needs to be done so that the biology learning process can run more optimally. This study aims to identify the need for Project Based Learning (PjBL)-based student worksheet's with socioscientific content, which will be developed as teaching materials to support the optimization of biology learning, especially in the material on environmental change and conservation. The method used in this research is qualitative, with a descriptive approach. The subjects used were 35 students of class 10.E7 of State Senior High School number 2 Padang Panjang. Data collection was carried out in three ways, namely observation of the school, surveys of students, and in-depth interviews with teachers. The instruments used are questionnaires and interview sheets. Through data collection, the results showed that Project-based learning has been implemented. However, there is no student worksheet with a project-based learning model with socioscientific content, especially on the material of environmental change and preservation. Therefore, it is necessary to develop PjBL-based student worksheets with socioscientific content on the material of environmental change and preservation in the Senior High School E phase. Keywords: Student Worksheet, Project Based Learning, Socioscientific